Non-Communicable Disease Early Detection Among Older Adults in Gorontalo: Baseline Findings for a Family-Centered Nursing Digital System - Rosmin Ilham; Rizal Lamusu; Ilyas Abas; Rona Febriyona (Poltekita: Jurnal Ilmu Kesehatan, 2026)
Background: Non-Communicable Diseases are a major health concern among the elderly, especially in developing regions such as Gorontalo, Indonesia. Early detection and continuous monitoring are often limited due to low health literacy, inadequate family involvement, and limited access to healthcare services. To address these challenges, the development of a Family Centered Nursing based digital system is proposed as an innovative approach to empower families in managing elderly health. This system aims to integrate digital health monitoring, family education, and early warning features to support preventive care and reduce complications among the elderly. Methods: A descriptive quantitative design was used, involving 125 elderly respondents and their families selected through purposive sampling. Data were collected using a structured questionnaire on non-communicable disease status and components of Family Centered Care, then analyzed using descriptive statistics. Results: The study findings indicate a high proportion of participants who screened positive for NCD indicators based on the early-detection checklist, with 114 of 125 (91.2%) classified as NCD-positive. Regarding Family-Centered Nursing (FCN), most families demonstrated low involvement, with 101 (80.8%) categorized as low and 24 (19.2%) categorized as high. These results suggest that family participation in older adults’ health monitoring and early detection remains limited, highlighting the need to strengthen family engagement and awareness to support preventive health behaviors and improve well-being and quality of life. Conclusion: This study highlights the importance of developing family-based digital systems to improve family involvement, health literacy, and disease prevention among older adults. The integration of digital tools such as health apps for early detection of NCDs can strengthen the role of families in supporting early detection, prevention, and management of noncommunicable diseases in older adults. By empowering families through accessible technology and tailored health information, this system can encourage continuous monitoring, timely intervention, and adherence to preventive practices.